2017
DOI: 10.1016/j.engstruct.2017.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Bond performance of deep embedment FRP bars epoxy-bonded into concrete

Abstract: With increasing numbers of strength-deficient concrete infrastructure assets, strengthening and repair of concrete structures is becoming an issue of international importance. This study examines the bond behaviour of deep embedment (DE) glass fibre reinforced polymer (GFRP) and carbon FRP (CFRP) bars embedded into concrete prisms using an epoxy adhesive. The experimentally investigated parameters were the embedment length, FRP bar type and diameter, concrete compressive strength and hole diameter. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Many studies have been conducted to investigate the bonding behavior between FRP/steel bars and normal concrete [21,22,23,24,25,26,27,28,29,30,31]. The key factors affecting bonding performance, such as rebar type, bar diameter, embedment length, confinement pressure, and concrete strength, have been studied based on either direct pull-out test or beam test [21,22,23,24,25,26,27,28,29,30,31,32,33]. Baena et al [21] carried out an experimental program consisting of 88 pull-out specimens by using carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP) bars, and these bars presented a bonding strength lower than the steel bars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted to investigate the bonding behavior between FRP/steel bars and normal concrete [21,22,23,24,25,26,27,28,29,30,31]. The key factors affecting bonding performance, such as rebar type, bar diameter, embedment length, confinement pressure, and concrete strength, have been studied based on either direct pull-out test or beam test [21,22,23,24,25,26,27,28,29,30,31,32,33]. Baena et al [21] carried out an experimental program consisting of 88 pull-out specimens by using carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP) bars, and these bars presented a bonding strength lower than the steel bars.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that doubling the embedment length reduced the average bonding strength by 25%. The dependence of bond strength on embedment length could be explained by the nonlinear stress distribution, since the nonlinear stress distribution is more evident in the case of the larger embedment length, which results in the lower average bonding strength [28,29]. Furthermore, some experimental and theoretical investigations have been carried out on the bond behavior of FRP/steel bars in SCC structures [32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen beams with ETS-strengthening bars tested by Bui et al (2020b), Breveglieri et al (2015) and Mofidi et al (2012), and 48 beams with NSMstrengthening laminates tested by Dias and Barros (2013) are utilized. The bond behaviors to determine the τ m , s m , s f values are collected from the studies by Lorenzis and Nanni 2002, Godat et al (2012), Caro et al (2017) and Bui et al (2020a) considering the correlations in the configuration and material properties between the bond test specimens and the NSM-FRPretrofitted or ETS-FRP-strengthened beams.…”
Section: Validation Of the Modelmentioning
confidence: 99%
“…The mechanical anchorage system could compensate for the bonding deficiency. Currently, there are a number of studies investigating the bond behavior of the ETS or NSM retrofitting system to concrete through pullout tests and bending tests (Nakaba et al 2001;Lorenzis and Nanni 2002;Teng et al 2006;Soliman et al 2011;Coelho et al 2015;Godat et al 2012;Caro et al 2017;Bui et al 2020aBui et al , 2020c. Those researches assessed the bond stress-slip relationship, modes of failure and bond strength under various effects such as the bonded length, concrete strength, FRP size and property.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the corrosion resistance of steel reinforcing bars, the fiber reinforced polymer (FRP) bar, which has the characteristics of corrosion resistance and high tensile strength, has become an ideal substitute for steel bars, due to its excellent mechanical properties. However, due to its low elastic modulus, FRP-reinforced concrete structures often have large deformations, large cracks and brittle failure characteristics [1][2][3][4]. The recent development of steel-FRP composite bars (SCFCB) makes up for the lack of ductility of FRP rebars to some extent, and reduces engineering costs [5,6].…”
Section: Introductionmentioning
confidence: 99%